Low Doses of Sucralose Alter Fecal Microbiota in High-Fat Diet-Induced Obese Rats - Zhang, Minchun; Chen, Jie; Yang, Minglan; Qian, Cheng; Liu, Yu; Qi, Yicheng; Feng, Rilu; Yang, Mei; Liu, Wei; Ma, Jing (Frontiers in Nutrition, 2021)
Artificial sweeteners (AS) have been widely used as sugar substitutes to reduce calorie intake. However, it was reported that high doses of AS induced glucose intolerance via modulating gut microbiota. The objective of this study was to investigate the effects of lower doses of sucralose on fecal microbiota in obesity. Eight weeks after high-fat diet (HFD), the male Sprague Dawley rats were randomly divided into four groups (6 in each group) and administrated by a daily gavage of 2 ml normal saline (CON), 0.54 mM sucralose (N054), 0.78 mM sucralose (N078), and 324 mM sucrose (S324), respectively. After 4 weeks, fecal samples were obtained and analyzed by 16S ribosomal RNA gene sequencing. The richness and diversity of fecal microbiota were not changed by sucralose or sucrose. Both 0.54 mM (0.43 mg) and 0.78 mM (0.62 mg) sucralose tended to reduce the beneficial bacteria, Lactobacillaceae and Akkermansiaceae. The relative abundance of family Acidaminoccaceae and its genus Phascolarctobacteriam were increased after 0.54 mM sucralose. In functional prediction, 0.54 mM sucralose increased profiles of carbohydrate metabolism, whereas 0.78 mM sucralose enhanced those of amino acid metabolism. The lower doses of sucralose might alter the compositions of fecal microbiota. The effects of sucralose in different dosages should be considered in the future study.